Barbra eaudiobook The way she is. - Andersen, Christopher (Tantor Media, 2006)
She is a one-name legend, a global icon, the ultimate diva. Yet most of what we know about Barbra Joan Streisand is the stuff of caricature: the Brooklyn girl made good, the ugly duckling who blossomed into a modern-day Nefertiti, the political dilettante driving to the barricades in her Rolls-Royce, the Oscar-winning actress and bona fide movie mogul, the greatest female singer who ever lived, a skinflint, a philanthropist, a connoisseur and a barbarian, the woman whose physical characteristics are instantly identifiable around the planet—the tapered nails, those slightly crossed eyes, that nose, the voice . Even to the multitudes around the world who idolize her, Streisand remains aloof, unknowable, tantalizingly beyond reach. Until now. In the manner of his number-one New York Times bestsellers The Day Diana Died and The Day John Died , Christopher Andersen taps into important sources—eyewitnesses to Streisand's remarkable life and career—to paint a startling portrait of the artist...and the woman. Whether you love her, hate her, or are simply spellbound by her titanic talent, Barbra is one thing above all others: a true American original.